Endometrial Mucin-1 Expression Increases In Mid-Diestrus Following PG-600 Administration in sheep - Hayder M.H. Habeeb; Ann Ramsey; Michelle A. Kutzler (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ)
Mucin-1 (MUC-1) is an anti-adhesion glycoprotein expressed on the apical surface of the endometrial luminal and glandular epithelium which prevents interactions between the trophectoderm and endometrial epithelium. The aim of this study was to investigate the outcome of PG-600 on ovine endometrial MUC-1 immunoexpression during early and mid-diestrus. Twenty-four cycling ewes (Polypay) were administered progesterone for 9 days. Two days before progesterone withdrawal, ewes were treated with cloprostenol. At progesterone withdrawal (d0), ewes were treated with either PG-600 (5 mL) or saline (5 mL) group. Endometrial tissues were collected surgically on days 4 and 7 after PG-600 or saline (n=6/group/timepoint) and were subjected to immunohistochemistry followed by image acquisition. Stained area for MUC-1 was quantified using Image J. The diestrous intercaruncular endometrium of both treated and control ewes expressed MUC-1. However, the percent area expressing MUC-1 varied between endometrial area (luminal and superficial glandular epithelium), time (day four, day 7), and treatment group. PG-600 treatment increased MUC-1 expression in the luminal epithelium on day 7 and in the superficial glandular epithelium expression on day 4. The results of this study show that administration of PG-600 to ewes increases endometrial MUC-1 expression in mid diestrus, which provides a possible mechanism for lower fertility found following treatment by PG-600 in sheep.